WATER TEMPERATURE AND ITS DIVERSITY IN THE DEEPEST LAKES OF THE TUCHOLA FOREST AND THE KASHUBIAN AND BRODNICKIE LAKELANDS - SKOWRON, RAJMUND; PIASECKI, ADAM (Bulletin of Geography. Physical Geography Series, 2015)
This study presents the results of monthly examinations of the vertical distribution of water thermal structure (2008–2011) carried out over a four-year period in the deepest lakes located in the Kashubian and Brodnickie Lakelands and the Tuchola Forest1. Three lakes were selected for examination (Raduńskie Górne, Zbiczno and Ostrowite). Their maximum depths slightly exceed 40 m, and their surface areas range from 121 to 362.5 ha. The results of the measurements show that, despite only minor differences in depth, water temperature varied significantly between the studied lakes. These differences were mainly apparent in the extent of the epilimnion, water thermal stratification, and in the water temperature in the bottom-most layers in summer and winter. The diversity in thermal stratification of the lakes is mainly determined by their morphometric properties, their location above sea level, and the dynamic influences of winds.